Spatial memory deficiency early in 6xTg Alzheimer’s disease mouse model - Shinwoo Kang; Jinho Kim; Keun-A Chang (Scientific Reports, 2021)
Abstract Alzheimer’s disease (AD) is mainly characterized by the deposition of extracellular amyloid plaques and intracellular accumulation of neurofibrillary tangles (NFTs). While the recent 5xFAD AD mouse model exhibits many AD-related phenotypes and a relatively early and aggressive amyloid β production, it does not show NFTs. Here, we developed and evaluated a novel AD mouse model (6xTg-AD, 6xTg) by crossbreeding 5xFAD mice with mice expressing mutant (P301L) tau protein (MAPT). Through behavioral and histopathological tests, we analyzed cognitive changes and neuropathology in 6xTg mice compared to their respective parental strains according to age. Spatial memory deficits occurred in 6xTg mice at 2 months of age, earlier than they occurred in 5xFAD mice. Histopathological data revealed aggressive Aβ42 and p-tau accumulation in 6xTg mice. Microglial activation occurred in the cortex and hippocampus of 6xTg mice beginning at 2 months. In 6xTg model mice, the synaptic loss was observed in the cortex from 4 months of age and in the hippocampus from 6 months of age, and neuronal loss appeared in the cortex from 4 months of age and in the hippocampus 6 months of age, earlier than it is observed in the 5xFAD and JNPL3 models. These results showed that each pathological symptom appeared much faster than in their parental animal models. In conclusion, these novel 6xTg-AD mice might be an advanced animal model for studying AD, representing a promising approach to developing effective therapy.